Strategi Pengelolaan Kawasan Kota Cina, Medan, Provinsi Sumatera Utara - Stanov Purnawibowo; Lucas Partanda Koestoro (Berkala Arkeologi Sangkhakala, 2015)
Kota Cina area is one of the areas along the east coast of North Sumatra, which is closely related to trade network in Southeast Asia since at least 12th to 14th centuries CE. Previous researchers have proven that the area had once been a thriving city of commerce, port, and settlement during the period. This research is aimed at fabricating a strategy to manage Kota Cina area. The strategy is oriented toward preservation and utilization for the sake of the community. The method used is retracing its management history, which can then be used as the basis for determining the management strategy in the future. The research has generated four strategies, namely to: assign Kota Cina as a cultural heritage area, establish a management institution, include active participation of local community members in developing this area as a tourist destination, and develop thorough research.